Inheritance of cucumber tolerance to Zucchini yellow mosaic virus - Cardoso, A. I.I. [UNESP]; Pavan, M. A. [UNESP]; Krause Sakate, R. [UNESP]; Fattori, K. [UNESP] (My University, 2010)
Studies were carried out in Brazil to study the inheritance of tolerance to Zucchini yellow mosaic virus (ZYMV) in cucumber cv. Formosa. This cultivar was individually crossed with two cucumber lines from different varietal types (Lb from a Brazilian type, and Lj from a Japanese type), both susceptible to the virus. Two experiments, one for each line, were separately carried out, where 6 treatments (parents, generations F1, F2 and F1BC1 for both parents) were evaluated in a randomized block design with 5 repetitions. Cotyledons of 2-week-old cucumber seedlings were inoculated with ZYMV. Only the plants that did not show symptoms up to 63 days post inoculation were considered as tolerant. A chi-square (χ2) analysis for assessing segregation from F2 and both F1BC1, led to the conclusion that the tolerance found in cv. Formosa is determined by a recessive gene.
Keywords: Breeding; Cucumis sativus; Genetics; Virus resistance; ZYMV